Pharyngeal microbiome alterations during Neisseria gonorrhoeae infection - Marangoni, Antonella; Ceccarani, Camilla; Camboni, Tania; Consolandi, Clarissa; Foschi, Claudio; Salvo, Melissa; Gaspari, Valeria; D’Antuono, Antonietta; Belletti, Matteo; Re, Maria Carla; Severgnini, Marco (PloS one, 2020)
Pharyngeal gonorrhoea is a common sexually transmitted infection among 'men having sex with other men' (MSM). Neisseria gonorrhoeae (NG) pharyngeal infections are usually characterized by the absence of symptoms, acting as an important reservoir for their further spread. To the best of our knowledge, no information about the composition of the pharyngeal microbiome during an ongoing NG infection is currently available. Therefore, in this study, we characterized the pharyngeal bacterial community profiles associated with NG infection in a well-selected cohort of HIV-negative MSM reporting unsafe oral intercourse. A total of 70 pharyngeal swabs were considered, comparing non-infected subjects (n = 45) versus patients with pharyngeal gonorrhoea (n = 25) whose microbiota composition was analyzed from pharyngeal swabs through sequencing of hypervariable V3-V4 regions of the 16S rRNA gene. The pharyngeal microbiome of all subjects was dominated by Prevotellaceae, Veillonellaceae and Streptococcaceae families. Patients with pharyngeal gonorrhoea harboured a pharyngeal microbiome quite similar to negative subjects. Nevertheless, when looking to less-represented bacterial species (relative abundance approximately 1% or less), an imbalance between aerobe and anaerobe microorganisms was observed in NG-infected patients. In particular, the pharyngeal microbiome of NG-positive individuals was richer in several anaerobes (e.g. Treponema, Parvimonas, Peptococcus, Catonella, Filifactor) and poorer in various aerobe genera (i.e. Pseudomonas, Escherichia), compared to non-infected controls. No significant differences were noticed in the distribution of commensal Neisseria species of the oropharynx between NG-positive and negative subjects. Metabolic variations induced by changes in the microbiome abundance were assessed by a functional prediction of the bacterial metabolic pathways: a more abundant involvement of D-glutamine and D-glutamate metabolism, carbohydrate metabolism, as well as a greater activation of the energy metabolism was observed in patients with pharyngeal gonorrhoea compared to non-infected individuals. Information about the bacterial composition of the pharyngeal microbiome in case of gonorrhoea could shed light on the pathogenesis of the infection and open new perspectives for the prevention and control of this condition.